Improving financial wellbeing in Indonesia: the role of social media as a mediating factor in financial behavior - Taufik Faturohman; Tarada Berlian Megananda; Henndy Ginting (Cogent Social Sciences, 2024)
This research examines the impact of an external locus of control, financial literacy, financial self-efficacy, an internal locus of control, and social media on financial well-being, focusing on the mediating role of financial behavior. Financial wellbeing can be improved by reducing the external locus of control, increasing individual financial self-efficacy and financial literacy, and using social media appropriately. Furthermore, the importance of financial behavior is emphasized by the indirect effects of external locus of control, financial literacy, financial self-efficacy, and social media on financial wellbeing. The study features an online survey questionnaire with 438 respondents. The relationships were investigated using PLS-SEM. According to the study’s findings, financial influencers are social media data variables that significantly affect financial behavior. These findings can assist policymakers, and business leaders in understanding the most influential factors affecting Indonesia’s financial wellbeing. Furthermore, the Indonesian government encourages the younger generation to improve its literacy index through public financial education. Research into financial wellbeing is critical because it aligns with the government’s goal of improving the stability and health of the population’s finances. Individuals can maintain financial control, allowing them to meet financial goals, manage unexpected expenses during emergencies, deal with financial problems, and enjoy life.